The Role of Antioxidant for Improving The Quality of Frozen Semen - Rizal, Muhammad; ., Herdis (Indonesian Animal Sciences Society, 2010)
The quality of frozen semen will be reduced if high oxidative metabolism activity in semen occurs, due to the formation of free radical compounds causing lipid peroxidation reaction on sperm plasma membrane. Lipid peroxidation occurs due to the exposure of semen to the oxygen during handling. Lipid peroxidation can be prevented by the addition of antioxidant compounds such as vitamin C, vitamin E, glutathione, and b-carotene, in the semen extender. Results of some researches showed that the addition of various antioxidans in extender can improve the quality of frozen semen of various animals. Key words: Antioxidant, free radical, lipid peroxidation, frozen semen